2004
DOI: 10.1577/a03-047.1
|View full text |Cite
|
Sign up to set email alerts
|

Hatchery Performance Attributes of Juvenile Lake Sturgeon Fed Two Natural Food Types

Abstract: The use of stocking programs to rehabilitate depressed populations of lake sturgeon Acipenser fulvescens requires the optimization of early life stage growth in hatchery settings. We evaluated the performance of juvenile lake sturgeon fed different proportions of two natural food types—adult brine shrimp Artemia spp. and larval bloodworms Chironomus spp.—over a 10‐week laboratory experiment. The following five diet treatments were provided: (1) 100% bloodworms; (2) 75% bloodworms : 25% brine shrimp; (3) 50% bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…For example, Stelzer et al (2008) analyzed the gut content of lake sturgeon in Lake Winnebago and found that gizzard shad (Dorosoma cepedianum) and Chironomus plumosus larvae comprise 56% and 33% of gut content mass, respectively, which was confirmed with a mixing model using ␦ 13 C and ␦ 15 N. Additionally, a study by Anderson et al (2012) and Choudhury et al (1996) confirmed the importance of Chironomidae in the Lake Winnebago diet and found that the chironomids were in high enough abundance to support the sturgeon. A diet study conducted by Volkman et al (2004) on juvenile lake sturgeon in hatcheries found that blood worms (Chironomus spp.) maximize growth, adding evidence to their importance in the wild.…”
Section: Dietmentioning
confidence: 99%
“…For example, Stelzer et al (2008) analyzed the gut content of lake sturgeon in Lake Winnebago and found that gizzard shad (Dorosoma cepedianum) and Chironomus plumosus larvae comprise 56% and 33% of gut content mass, respectively, which was confirmed with a mixing model using ␦ 13 C and ␦ 15 N. Additionally, a study by Anderson et al (2012) and Choudhury et al (1996) confirmed the importance of Chironomidae in the Lake Winnebago diet and found that the chironomids were in high enough abundance to support the sturgeon. A diet study conducted by Volkman et al (2004) on juvenile lake sturgeon in hatcheries found that blood worms (Chironomus spp.) maximize growth, adding evidence to their importance in the wild.…”
Section: Dietmentioning
confidence: 99%
“…Larval growth and ascorbic acid analysis.-Growth performance included weight gain (WG), daily absolute growth rate for length (AGR L ) and weight (AGR W ), specific growth rate in length (SGR L ) and weight (SGR W ), body weight increase (BWI) and feed conversion efficiency (FCE), which were evaluated according to the following production criteria (Volkman et al 2004;Falahatkar et al 2006):…”
Section: Methodsmentioning
confidence: 99%
“…The main problems of using live feed for fish larval rearing are availability and price (Cahu and Zambonino 2001), and many fish farmers can benefit from calculating feed efficiency. Volkman et al (2004) compared nonenriched frozen chironomids with Artemia spp. in feeding juvenile Lake Sturgeon Acipenser fulvescens; they found significantly higher FCE, WG, AGR W and SGR W in fish fed chironomids, which partially supports our results.…”
Section: Downloaded By [Tulane University] At 22:08 26 September 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…This has prompted a great deal of interest in the develop-ment of an artificial larval microdiet (MD) as an economic alternative to live food. The successful use of Artemia nauplii alone or co-fed with a commercial diet at the start feeding or during early development of different sturgeon species has been reported by a number of researchers (Bardi et al 1998;Dilauro, Krise & Fynn-Aikins 1998;Mohler, Kim King & Farrell 2000;Volkman, Pangle, Rajchel & Sutton 2004). This may be due to the composition, palatability or physical characteristics of the dry feed (Person Le Ruyet, Alexandre, Thebaud & Mugnier 1993), to the larva's inability to properly digest the feed (Holt 1993;Kolkovski, Tandler, Kissil & Gertler 1993;Walford & Lam 1993;Zambonino Infante & Cahu 1994), or to the low attractiveness of the non-mobile particle for the fish larva.…”
Section: Introductionmentioning
confidence: 99%